BRIEF ANALYSIS OF SUPPORTING FACTORS, INHIBITING FACTORS AND MARKETING STRATEGIES FOR CATFISH FARMING - Dadiono, Muh. Sulaiman; Kusuma, Rima Oktavia (Program Studi Teknologi Hasil Perikanan|Fakultas Pertanian|Universitas PGRI Banyuwangi, 2022)
Catfish cultivators in Indonesia often experience problems related to marketing strategies, supporting factors and inhibiting factors in catfish farming. So a brief analysis of the supporting factors, inhibiting factors and marketing strategies for catfish farming is needed in order to provide a brief description of catfish farmers in Indonesia. data collection was fully carried out by literature study. Secondary data was collected by reviewing references in the form of journals, books and online articles. Data search was carried out using the Google search engine or Google schoolar with the keywords catfish farming marketing strategy. The data obtained were then analyzed using descriptive methods. From the results of the study it was found that there is a need for special attention to the supporting factors for catfish cultivation, namely consumer interest, availability of seeds, superior catfish seeds, environmental cleanliness, and smooth marketing networks. It is also necessary to pay attention to inhibiting factors such as the promotion techniques used are ineffective and lack of marketing network, low productivity, low seed quality and quantity, high feed prices, lack of treatment for disease emergence, limited information technology and markets, risk of declining fish quality in transport. Marketing strategies must keep up with the times by utilizing digital marketing such as market place platforms and social media.